The semantic web: ESWC 2014 satellite events : ESWC 2014 Satellite Events, Anissaras, Crete, Greece, May 25-29, 2014, Revised Selected Papers - Blomqvist, Eva; Troncy, Raphael; Sack, Harald; Papadakis, Ioannis; Tordai, Anna; Presutti, Valentina (Lecture Notes in Computer Science, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the Satellite Events of the 11th International Conference on the Semantic Web, ESWC 2014, held in Anissaras, Crete, Greece, in May 2014. The volume contains 20 poster and 43 demonstration papers, selected from 113 submissions, as well as 12 best workshop papers selected from 60 papers presented at the workshop at ESWC 2014. Best two papers from AI Mashup Challenge are also included. The papers cover various aspects of the Semantic Web.